Phytochemical analysis of the methanolic leaves extract of Niedenzuella multiglandulosa (Malpighiaceae), a plant species toxic to cattle in Brazil - Mannochio Russo, Helena [UNESP]; Ferreira Queiroz, Emerson; Marcourt, Laurence; Rutz, Adriano; Allard, Pierre-Marie; de Almeida, Rafael Felipe; Marques Carvalho, Nilton; Wolfender, Jean-Luc; da Silva Bolzani, Vanderlan [UNESP] (Elsevier, 2020)
Niedenzuella multiglandulosa (Malpighiaceae) is a neotropical liana responsible for cattle intoxication outbreaks in Brazil that may lead to abortion and even death of the animals, causing substantial losses in Brazilian trade balance. A phytochemical study of N. multiglandulosa leaves was performed in order to obtain chemical information about secondary metabolites of this poorly studied species. The methanolic extract was purified by medium pressure liquid chromatography (MPLC) combined with semi preparative HPLC-PDA leading to the isolation of 16 compounds, including a new steroid named 5-hydroxypodecdysone B (13). The structure of the isolated compounds was determined by classical spectroscopic methods such as NMR and HRMS. Complementary 19F NMR and UPLC-HRMS analysis did not detect the presence of monofluoracetate (MFA), a toxic compound previously described from this species.
Keywords: Cattle intoxication; Isolation steroids; Metabolite profile; Monofluoracetate (MFA); Niedenzuella multiglandulosa; UHPLC-PDA-HRMS